“Determinants Of Purchase Decision Of Green Products Among The Customers In Bangalore City” - Mr. Prasanna H N, Dr. S.Saravanakumar (South Eastern European Journal of Public Health, 2025)
This research study is on the green marketing but specifically on determinants of purchase decision of green products. It has now been a global concern to protect environment form pollution caused by humans. With this vital information through the research provided by different researchers and expertise, companies have understood the importance and value of green marketing in business also. This information is the basis of literature of this research study. The objective of this research is influence of four traditional marketing mix elements, satisfaction and word of mouth attitude and purchasing intentions of consumers on eco-friendly products specifically on fasting moving consumer goods or non-durable ones. The purpose of this study is to find out the behaviour of consumer toward green product and collect information on the same. Our findings indicate that consumers already buying eco-friendly products and those who are satisfied by the previous purchases were willing to repeat purchases. Indeed satisfaction goes with purchase intention. Furthermore the importance of WOM and Advertisement about green products the fact that consumers believe in green claim explain the variance of the purchase intention. Our findings demonstrated that there were differences in attitudes and purchase intention toward green products between mainly the women and men.